PENGARUH SIMPANAN NASABAH TERHADAP LABA BERSIH BANK CENTRAL ASIA DAN BANK RAKYAT INDONESIA PERIODE 2020-2023 - Nathanael Gunawan, Aurelius; Tiur Manurung, Elizabeth (Universitas Muhammadiyah Metro, 2025)
This study analyzes the impact of customer deposits on net income at two of Indonesia's largest banks, PT Bank Central Asia Tbk and PT Bank Rakyat Indonesia Tbk. Financial data were obtained from financial reports over 32 quarters and analyzed using simple linear regression. The results show that customer deposits have a positive and significant effect on net income. The resulting linear regression equation indicates that an increase in customer deposits by one unit will raise net income by 0.05169315 units. Conversely, if customer deposits are zero, the bank's net income will decrease by -30526172.64 units. Customer deposits collected by banks are used to finance loans that generate interest income, a key component of bank profits. This study's findings align with previous research, which demonstrated that third-party funds, including time deposits, significantly influence banks' net income. The study underscores the importance of optimizing customer deposit management to support the financial performance of banks.